Near infrared absorbing glass and near infrared cut filters

By optimizing the glass composition of the near-infrared cutoff filter, reducing the use of copper ions, increasing the phosphate and oxygen ions content, and controlling the melt temperature of the glass, the problem of degradation of the existing filters during thinning is solved, efficient near-infrared cutoff and visible light transmission mittance, and improving chemical stability.

JP7662535B2Active Publication Date: 2025-04-15HOYA CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021567712
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-27
Filing Date
2020-12-25
Publication Date
2025-04-15
Estimated Expiration
2040-12-25

AI Technical Summary

Technical Problem

The existing near-infrared cutoff filters are difficult to maintain efficient near-infrared cutoff capability and visible light transmission during thinning, and at the same time, they lack sufficient chemical stability in high-temperature and high humidity environments.

Method used

By optimizing the composition of the glass, the amount of copper ions (Cu2+) is reduced, and the melting property and moisture stability of the glass are improved by adjusting the melt temperature and composition ratio of the glass. Specific measures include increasing the content of phosphate ions (P-ion) and oxygen ions (O-ion) in the glass, controlling the content of copper ions to 15.0% or less, and maintaining the total content of aluminum and phosphorus to 40.0% or more to achieve better near-infrared cutoff and visible light transmission.

Benefits of technology

It realizes the efficient near-infrared cutoff capability, visible light transmission and chemical stability of the near-infrared cutoff filter, which is suitable for high temperature and high humidity environments, and improves the overall performance of the filter.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662535000019
    Figure 0007662535000019
  • Figure 0007662535000001
    Figure 0007662535000001
  • Figure 0007662535000002
    Figure 0007662535000002
Patent Text Reader

Abstract

Provided is near-infrared absorbing glass including at least, as constituent ions thereof, one or more types of ion selected from the group consisting of P ions, Cu ions, O ions, Li ions, Na ions, and K ions, and one or more types of ion selected from the group consisting of Mg ions, Ca ions, Sr ions, and Ba ions, wherein: in the glass composition as expressed by cation%, the amount of Cu ions is not more than 15.0 cation%, and the amount of P ions is not more than 55.0 cation%; the cation ratio ((Al ions + P ions) / (Mg ions + Ca ions + Sr ions + Ba ions + Zn ions + Cu ions)) of the total amount of Al ions and P ions to the total amount of Mg ions, Ca ions, Sr ions, Ba ions, Zn ions, and Cu ions is not more than 5.300; the cation ratio ((Mg ions + Ca ions + Sr ions + Ba ions) / (Li ions + Na ions + K ions)) of the total amount of Mg ions, Ca ions, Sr ions, and Ba ions to the total amount of Li ions, Na ions, and K ions is not less than 0.100; the average valence of cations excluding Cu ions and P ions is less than 1.500; in the glass composition as expressed by anion%, the amount of O ions is not less than 85.0 anion%; and the ratio (O ions / P ions) of the amount of O ions to the amount of P ions is not less than 3.300. Also provided is a near-infrared cut filter comprising this near-infrared absorbing glass.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a near-infrared absorbing glass and a near-infrared cut filter. [Background technology]

[0002] Near-infrared cut filters have the function of cutting out unnecessary near-infrared light (wavelengths 700 to 1200 nm) in the sensitivity wavelength range of an image sensor, so that the light entering an image sensor such as a CCD or CMOS has a light wavelength distribution corresponding to the human visual sensitivity curve. Near-infrared cut filters are generally installed immediately before the image sensor.

[0003] Near-infrared cut filters that are widely used have a substrate made of near-infrared absorbing glass and are polished into a flat plate.

[0004] Near-infrared absorbing glass generally contains Cu ions. An example of the spectral transmittance characteristics of near-infrared absorbing glass is shown in FIG. 1. Note that FIG. 1 does not limit the present invention in any way. The light absorption characteristics in the vicinity of wavelengths of 700 to 1200 nm are due to the presence of Cu ions (Cu 2+ ) is expressed by the Cu ion (Cu phosphate glass). 2+ ) can exhibit the near-infrared absorption characteristics over a wide wavelength range, making it useful as glass for near-infrared cut filters (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2019-38719 A

[0006] In the transmittance curve for wavelengths of 600 nm and above in Figure 1, the wavelength at which the transmittance is 50% is called the "half value" and is one of the main standards for near-infrared cut filters. The half value varies depending on the filter specifications, but is often set to a wavelength range of 600 nm to 650 nm. A common method for setting the half value to a desired value is to follow the Beer-Lambert law and adjust the thickness of the glass substrate or the concentration of Cu ions (Cu 2+ ) There are ways to adjust either the concentration. Summary of the Invention [Problem to be solved by the invention]

[0007] A near-infrared cut filter is required to have an excellent ability to cut near-infrared rays (that is, low transmittance of near-infrared light while having a desired half-value), as well as high transmittance of visible light (wavelength 400 to 600 nm).

[0008] In recent years, imaging element modules mounted on smartphones and other devices are required to be both compact and high performance, and this has led to a demand for thinner near-infrared cut filters. In order to make the filters thinner while maintaining their ability to cut near-infrared rays, the Cu ions (Cu 2+ However, if the ratio of Cu in the glass raw materials is simply increased to achieve this, the Cu content will increase during melting. 2+ is reduced to Cu + It is known that the transmittance at a wavelength of about 400 nm in particular decreases.

[0009] Furthermore, in order to maintain transmittance characteristics under various usage environments, it is desirable for the near-infrared cut filter to have high chemical durability in high-temperature and high-humidity environments (that is, excellent weather resistance).

[0010] In view of the above, an object of one aspect of the present invention is to provide a near-infrared absorbing glass having excellent near-infrared cutting ability, high visible light transmittance and excellent weather resistance, and a near-infrared cut filter made of such a near-infrared absorbing glass. [Means for solving the problem]

[0011] In order to increase the visible light transmittance, the present inventors have investigated the glass composition from the following two perspectives. (1) A glass composition that achieves the desired half-value and sufficient near-infrared blocking ability even with a smaller amount of Cu than conventional glass compositions. (2) Cu when melted + In order to suppress the generation of SiO2, it is effective to melt and mold the glass at a lower temperature. Therefore, the glass composition has better melting properties for the raw material batch than before.

[0012] Regarding (1), the inventors 2+ By assuming a complex glass skeleton in which P2O5 is arranged around Cu, and decreasing the average valence of the monovalent and divalent ions that are intermediate components other than the glass skeleton, Cu 2+ Inflow of electrons to Cu + It is possible to suppress the generation of Cu 2+ It was found that the optical absorption wavelength region of the ZnO film shifts to shorter wavelengths, and the amount of Cu required to achieve the desired half-value can be reduced.

[0013] Regarding (2), the inventors discovered that by controlling the ratio of glass network-forming components such as Al and P to a certain level or less, the meltability of the glass raw material batch can be improved, making it possible to melt and form the glass at a lower temperature than before.

[0014] Furthermore, the inventors have found that by setting the ratio of O to P in the entire glass to a certain level or more, the amount of Cu required to achieve the desired half value can be reduced, and further, it is possible to improve weather resistance by suppressing the formation of cross-linking bonds of POPs, which have poor water resistance.

[0015] That is, one aspect of the present invention is The constituent ions are: P ions, Cu ions, O ion, One or more ions selected from the group consisting of Li ions, Na ions, and K ions, and one or more ions selected from the group consisting of Mg ions, Ca ions, Sr ions, and Ba ions; At least In the glass composition expressed in cation percentage, The Cu ion content is 15.0 cation % or less, The P ion content is 55.0 cation% or less, a cation ratio ((Al ion + P ion) / (Mg ion + Ca ion + Sr ion + Ba ion + Zn ion + Cu ion)) of the total content of Al ion and P ion to the total content of Mg ion, Ca ion, Sr ion, Ba ion, Zn ion, and Cu ion is 5.300 or less, a cation ratio ((Mg ions + Ca ions + Sr ions + Ba ions) / (Li ions + Na ions + K ions)) of the total content of Mg ions, Ca ions, Sr ions and Ba ions to the total content of Li ions, Na ions and K ions is 0.100 or more, The average valence of cations other than Cu ions and P ions is less than 1.500, In the glass composition shown in anion %: The content of O ions is 85.0 anion% or more, and A near-infrared absorbing glass having a ratio of O ion content to P ion content (O ion / P ion) of 3.300 or more (hereinafter, also simply referred to as "glass"); Regarding.

[0016] The near-infrared absorbing glass has the above glass composition and thus can have excellent near-infrared cutting ability, high visible light transmittance, and excellent weather resistance and meltability. Effect of the Invention

[0017] According to one aspect of the present invention, there is provided a near-infrared absorbing glass having excellent near-infrared cutting ability, high visible light transmittance, and excellent weather resistance and meltability. Furthermore, according to another aspect of the present invention, there is provided a near-infrared cut filter made of such near-infrared absorbing glass. [Brief description of the drawings]

[0018] [Figure 1] 2 shows an example of the spectral transmittance characteristics of near-infrared absorbing glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] [Near infrared absorbing glass] In the present invention and this specification, near-infrared absorbing glass refers to glass that has the property of absorbing light in at least the entire region or part of the wavelengths in the near-infrared wavelength range (wavelengths of 700 to 1200 nm). Furthermore, the near-infrared absorbing glass according to one embodiment of the present invention can be an oxide glass since it contains O ions (oxygen ions) as constituent ions. The oxide glass is a glass in which the main network-forming component of the glass is an oxide. Furthermore, the near-infrared absorbing glass according to one embodiment of the present invention can be a phosphate glass since it contains P ions (phosphorus ions) as well as O ions (oxygen ions) as constituent ions.

[0020] The near infrared absorbing glass will now be described in more detail.

[0021] <Glass composition> In the present invention and this specification, the content and total content of cations (cationic components) are expressed in cation % unless otherwise specified, and the content and total content of anions (anionic components) are expressed in anion % unless otherwise specified. Here, "cation %" is a value calculated by "(number of cations of interest / total number of cations in glass components) x 100" and means the molar percentage of the amount of cations of interest relative to the total amount of cations. Furthermore, "anion %" is a value calculated by "(number of anions of interest / total number of anions in the glass components) x 100" and means the molar percentage of the amount of the anion of interest relative to the total amount of anions. The molar ratio of the contents of cations to each other is equal to the ratio of the contents of the cations in question, expressed as cation %, and the molar ratio of the contents of anions to each other is equal to the ratio of the contents of the anions in question, expressed as anion %. The molar ratio of the cation content to the anion content is the ratio of the contents (expressed in mol %) of the components of interest when the total amount of all cations and all anions is taken as 100 mol %. The content of each component can be determined by quantifying the content (mass % of element) of the element contained in the glass by a known method, such as inductively coupled plasma atomic emission spectrometry (ICP-AES), inductively coupled plasma mass spectrometry (ICP-MS), ion chromatography, etc. The content of each element expressed in mol % can be obtained by dividing the content (mass % of element) of the element by the atomic weight, and the cation % and anion % can be obtained from the value. In the present invention and this specification, the content of a component being 0% or not being contained or not being introduced means that the component is substantially not contained, and it is acceptable for the component to be contained at an unavoidable impurity level. The unavoidable impurity level means, for example, less than 0.01%.

[0022] Regarding the valence of cations, the formal valence of each cation is used to calculate the average valence, which will be described in detail later. The formal valence is the valence required for an oxide of a given cation to maintain electrical neutrality when the valence of the oxygen ion (anion) that constitutes the oxide is set to -2, and can be uniquely determined from the chemical formula of the oxide. For example, for Cu ions, the O 2- To maintain electrical neutrality between and Cu, the valence of Cu is +2. For example, for P ions, the O 2- To maintain the electrical neutrality between and P, the valence of P is +5. This can be generalized to cation AX O Y The formal valence of is +2X / Y. Therefore, when analyzing glass composition, it is not necessary to analyze the valence of the cation. The formal valence of the anion (for example, the valence of the oxygen ion is -2) is also based on the idea that the oxygen ion accepts two electrons and forms a closed shell structure. Therefore, when analyzing glass composition, it is not necessary to analyze the valence of the anion. Also, as mentioned above, 2+ A part of Cu is melted. + However, since the amount is small, the valence of all Cu can be considered to be +2 when calculating the average valence.

[0023] (Cations) P ions are a network-forming component of glass. From the viewpoint of improving weather resistance and meltability, the P ion content of the glass is 55.0% or less, preferably 53.0% or less, more preferably 51.0% or less, even more preferably 50.0% or less, even more preferably 49.0% or less, even more preferably 48.0% or less, even more preferably 47.0% or less, even more preferably 46.0% or less, even more preferably 45.0% or less, and even more preferably 44.0% or less. Since the glass contains P ions as a constituent ion, the P ion content is more than 0%. From the viewpoints of improving the devitrification resistance during glass melting and improving the mechanical strength of the glass, the P ion content is preferably 30.0% or more, more preferably 32.0% or more, even more preferably 34.0% or more, still more preferably 36.0% or more, even more preferably 38.0% or more, still more preferably 39.0% or more, still more preferably 40.0% or more, and still more preferably 41.0% or more. The formal valence of the P ion is +5.

[0024] Cu ions are a component that contributes to imparting near-infrared cut-off capability to the glass. From the viewpoint of increasing the visible light transmittance, the Cu ion content of the glass is 15.0% or less, preferably 13.0% or less, more preferably 11.0% or less, and even more preferably 9.0% or less. Since the glass contains Cu ions as constituent ions, the Cu ion content is more than 0%. In order to have sufficient near-infrared cut-off capability, the Cu ion content is preferably 0.5% or more, more preferably 1.5% or more, and even more preferably 2.5% or more. As will be described in detail later, in one embodiment, the above glass can be used as a glass for a near-infrared cut filter having a thickness of 0.25 mm or less. For glass (hereinafter also referred to as "glass I") suitable for a near-infrared cut filter having a relatively thin thickness within the above thickness range, the Cu ion content is preferably 1.5% or more, and more preferably in the following order: 1.7% or more, 1.9% or more, 2.1% or more, 2.3% or more, 2.5% or more, 2.7% or more, 2.9% or more, 3.1% or more, 3.3% or more, 3.5% or more, 3.7% or more, 3.9% or more, 4.1% or more, 4.5% or more, 4.7% or more, 4.9% or more, and 5.1% or more. From the viewpoint of further increasing the visible light transmittance in such a near-infrared cut filter, the Cu ion content in Glass I is preferably 15.0% or less, and more preferably 13.0% or less, 11.0% or less, 10.0% or less, 9.0% or less, 8.5% or less, 8.0% or less, 7.5% or less, 7.0% or less, 6.5% or less, and 6.0% or less, in that order. The preferred value of Cu ions to be contained in glass suitable for a near-infrared cut filter having a desired thickness can be obtained by multiplying the above preferred range by (0.11 / d), where d is the thickness for which the preferred value of Cu ions is to be obtained, and is expressed in mm. In addition, with regard to a glass (hereinafter also referred to as "glass II") suitable for a near-infrared cut filter having a relatively large thickness within the thickness range of 0.25 mm or less, in one embodiment, a preferable range of Cu ions can be obtained by multiplying the above-mentioned preferable range by (0.11 / d). In addition, in one embodiment, the Cu ion content of glass II is preferably 0.5% or more, more preferably 0.7% or more, 0.9% or more, 1.1% or more, 1.3% or more, 1.5% or more, 1.7% or more, 1.9% or more, 2.1% or more, 2.3% or more, and 2.5% or more in that order. In addition, from the viewpoint of further increasing the visible light transmittance in such a near-infrared cut filter, in one embodiment, the Cu ion content of glass II is preferably 10.0% or less, more preferably 9.0% or less, 8.5% or less, 8.0% or less, 7.5% or less, 7.0% or less, 6.5% or less, 6.0% or less, 5.5% or less, 5.0% or less, 4.5% or less, 4.0% or less, and 3.5% or less in that order. The formal valence of the Cu ion is +2.

[0025] The Li ion content of the above glass can be 0%, 0% or more, or more than 0%. Li ions are a component that has the function of improving the devitrification resistance of the glass during melting and forming. From the viewpoint of enhancing the meltability of the glass, the Li ion content is preferably 10.0% or more, more preferably 12.0% or more, even more preferably 13.0% or more, even more preferably 14.0% or more, even more preferably 15.0% or more, even more preferably 16.0% or more, even more preferably 17.0% or more, even more preferably 18.0% or more, even more preferably 20.0% or more, even more preferably 20.5% or more, even more preferably 21.0% or more, and even more preferably in the following order: 21.5% or more, 22.0% or more, 22.5% or more, 23.0% or more, 23.5% or more, 24.0% or more, 24.5% or more, 25.0% or more, 25.5% or more, and 26.0% or more. From the viewpoint of improving the chemical durability and / or processability of the glass or increasing the liquidus viscosity of the glass, the Li ion content is preferably 32.0% or less, more preferably 31.0% or less, even more preferably 30.5% or less, even more preferably 30.0% or less, even more preferably 29.5% or less, even more preferably 29.0% or less, even more preferably 28.5% or less, even more preferably 28.0% or less, and particularly more preferably 27.5% or less. The formal valence of the Li ion is +1. In one embodiment, from the viewpoint, it is preferable that the "Li ion content>Na ion content" and it is preferable that the "Li ion content>K ion content".

[0026] The Na ion content of the above glass can be 0%, 0% or more, or more than 0%. Na ions are also components that function to improve the meltability of the glass. In one form, it is preferable to mainly use Li or K. Specifically, from the viewpoints of improving the devitrification resistance of the glass, improving the viscosity at the liquidus temperature, and improving the chemical durability and / or processability, the Na ion content is preferably 30.0% or less, more preferably 28.0% or less, still more preferably 27.0% or less, even more preferably 25.0% or less, yet more preferably 23.0% or less, still more preferably 21.0% or less, even more preferably 19.0% or less, yet even more preferably 17.0% or less, still even more preferably 15.0% or less, still even more preferably 13.0% or less, and further preferably 11.0% or less, 10.0% or less, 9.0% or less, 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, 2.0 % Hereinafter, 1.0 % Hereinafter, 0.5 % The following are even more preferable in this order. The formal valence of Na ions is +1. In one form, from the above viewpoints, it is preferable that "Na ion content < Li ion content", and it is preferable that "Na ion content < K ion content".

[0027] The K ion content of the above glass can be 0%, 0% or more, or more than 0%. K ions are also components that improve the meltability of the glass and further improve the devitrification resistance during melting and forming. From these viewpoints, the K ion content is preferably 3.0% or more, more preferably 4.0% or more, still more preferably 5.0% or more, even more preferably 6.0% or more, even still more preferably 7.0% or more, yet even more preferably 8.0% or more, yet still more preferably 9.0% or more, and yet even still more preferably 10.0% or more. On the other hand, from the viewpoints of improving the viscosity at the liquidus temperature of the glass, improving chemical durability and / or processability, the K ion content is preferably 20.0% or less, more preferably 19.0% or less, still more preferably 17.0% or less, even more preferably 15.0% or less, even still more preferably 14.5% or less, even still more preferably 14.0% or less, yet even more preferably 13.5% or less, yet still more preferably 13.0% or less, and yet even still more preferably 12.5% or less, and particularly preferably 12.3% or less. The formal valence of K ions is +1. In one form, from the above viewpoints, it is preferable that "K ion content < Li ion content", and it is preferable that "K ion content > Na ion content".

[0028] The above glass contains, as constituent ions, one or more ions selected from the group consisting of Li ions, Na ions and K ions. That is, in one form, the above glass can contain only Li ions, in another form it can contain only Na ions, in another form it can contain only K ions, in another form it can contain Li ions and Na ions, in another form it can contain Li ions and K ions, in another form it can contain Na ions and K ions, and in still another form it can contain Li ions, Na ions and K ions.

[0029] The glass may also contain other alkali metal ions other than Li, Na and K ions. The other alkali metal ions may include Cs ions. The Cs ion content of the glass may be 0%, 0% or more, or greater than 0%. The formal valence of the Cs ion is +1.

[0030] From the viewpoint of decreasing the average valence and increasing the visible light transmittance, the total content of Li ions, Na ions and K ions is preferably 19.0% or more, more preferably 21.0% or more, even more preferably 23.0% or more, still more preferably 25.0% or more, even more preferably 27.0% or more, even more preferably 28.0% or more, even more preferably 29.0% or more, and still more preferably 30.0% or more. It is even more preferable that the content is 30.5% or more, even more preferable that the content is 31.0% or more, and further, it is more preferable that the content is 32.0% or more, 32.5% or more, 33.0% or more, 33.5% or more, 34.0% or more, 34.5% or more, 35.0% or more, 35.5% or more, 36.0% or more, 36.5% or more, 37.0% or more, 37.5% or more, 38.0% or more, 38.5% or more, 39.0% or more, and 39.1% or more in this order. Furthermore, from the viewpoint of further improving weather resistance, suppressing a decrease in the glass transition temperature, and / or suppressing a decrease in viscosity at the liquidus temperature, the total content of Li ions, Na ions, and K ions is preferably 56.0% or less, more preferably 54.0% or less, even more preferably 52.0% or less, still more preferably 50.0% or less, still more preferably 48.0% or less, even more preferably 46.0% or less, even more preferably 45.0% or less, and still more preferably in the following order: 44.0% or less, 43.0% or less, 42.5% or less, 42.0% or less, 41.5% or less, 41.0% or less, 40.5% or less, 40.0% or less, and still more preferably 39.5% or less.

[0031] The Mg ion content of the glass can be 0%, 0% or more, or more than 0%. From the viewpoints of suppressing the decrease in the liquid-phase viscosity of the glass, reinforcing the mechanical strength of the glass, and / or reinforcing the chemical resistance, the Mg ion content is preferably 0.3% or more, more preferably 0.5% or more, still more preferably 0.8% or more, even more preferably 1.1% or more, and yet even more preferably 1.3% or more. Further, from the viewpoint of further improving the devitrification resistance during melting and forming, the Mg ion content is preferably 7.0% or less, more preferably 6.0% or less, % still more preferably 5.0% or less, even more preferably 4.0% or less, yet even more preferably 3.5% or less, still even more preferably 3.0% or less, yet still even more preferably 2.5% or less, yet even more preferably 2.0% or less, and yet even more preferably 1.8% or less. The formal valence of the Mg ion is +2. In one form, from the above viewpoints, it is preferable that "Mg ion content < Ca ion content", and it is preferable that "Mg ion content < Ba ion content".

[0032] The Ca ion content of the above glass can be 0%, 0% or more, or more than 0%. From the viewpoints of suppressing a decrease in the liquidus viscosity of the glass, reinforcing the mechanical strength of the glass, and reinforcing the chemical resistance, the Ca ion content is preferably 1.3% or more, more preferably 1.5% or more, even more preferably 1.7% or more, still more preferably 1.9% or more, even more preferably 2.1% or more, even more preferably 2.3% or more, even more preferably 2.5% or more, and particularly preferably 2.7% or more. From the viewpoint of further improving the devitrification resistance during melting and molding, the Ca ion content is preferably 9.0% or less, more preferably 8.0% or less, even more preferably 7.0% or less, even more preferably 6.0% or less, even more preferably 5.0% or less, even more preferably 4.5% or less, even more preferably 4.2% or less, even more preferably 3.9% or less, even more preferably 3.7% or less, and particularly preferably 3.5% or less. The formal valence of Ca ions is +2. In one embodiment, from the above viewpoint, it is preferable that "Ca ion content>Mg ion content" and "Ca ion content>Sr ion content" are satisfied.

[0033] The Sr ion content of the glass can be 0%, 0% or more, or more than 0%. From the viewpoints of suppressing the decrease in the liquid-phase viscosity of the glass, reinforcing the mechanical strength of the glass, and reinforcing the chemical resistance, the Sr ion content is preferably 0.2% or more, more preferably 0.4% or more, still more preferably 0.6% or more, even more preferably 0.8% or more, and yet more preferably 0.9% or more. Further, from the viewpoint of further improving the devitrification resistance during melting and forming, the Sr ion content is preferably 4.0% or less, more preferably 3.5% or less, still more preferably 3.3% or less, even more preferably 3.1% or less, yet more preferably 2.7% or less, still more preferably 2.5% or less, even more preferably 2.3% or less, yet even more preferably 2.1% or less, still even more preferably 1.9% or less, yet still even more preferably 1.7% or less, and particularly preferably 1.5% or less. The formal valence of Sr ions is +2. In one form, from the above viewpoints, it is preferable that "Sr ion content < Ca ion content", and it is preferable that "Sr ion content < Ba ion content".

[0034] The Ba ion content of the above glass can be 0%, 0% or more, or more than 0%. From the viewpoints of suppressing a decrease in the liquidus viscosity of the glass, reinforcing the mechanical strength of the glass, and reinforcing the chemical resistance, the Ba ion content is preferably 1.5% or more, more preferably 2.5% or more, even more preferably 2.9% or more, still more preferably 3.1% or more, even more preferably 3.3% or more, and still more preferably 3.5% or more. From the viewpoint of further improving the devitrification resistance during melting and molding, the Ba ion content is preferably 10.0% or less, more preferably 9.5% or less, even more preferably 9.0% or less, even more preferably 8.5% or less, even more preferably 8.0% or less, even more preferably 7.5% or less, even more preferably 7.0% or less, even more preferably 6.5% or less, even more preferably 6.0% or less, even more preferably 5.6% or less, even more preferably 5.3% or less, and even more preferably 5.0% or less, 4.7% or less, 4.5% or less, and 4.3% or less. The formal valence of Ba ions is +2. In one embodiment, from the above viewpoint, it is preferable that "Ba ion content>Ca ion content" and it is preferable that "Ba ion content>Sr ion content".

[0035] The glass contains one or more ions selected from the group consisting of Mg ions, Ca ions, Sr ions, and Ba ions. From the viewpoint of decreasing the average valence and increasing the visible light transmittance, it is preferable that the total content of Mg ions, Ca ions, Sr ions, and Ba ions is small. From the above viewpoint and from the viewpoint of further improving the meltability, the total content of Mg ions, Ca ions, Sr ions and Ba ions is preferably 20.0% or less, more preferably 19.0% or less, even more preferably 18.0% or less, even more preferably 17.5% or less, more preferably 17.0% or less, even more preferably 16.5% or less, even more preferably 16.0% or less, even more preferably 15.5% or less, even more preferably 15.0% or less, even more preferably 14.5% or less, even more preferably 14.0% or less, and even more preferably in the following order: 13.5% or less, 13.0% or less, 12.5% ​​or less, 12.0% or less, 11.0% or less, 10.5% or less, and 10.0% or less. Furthermore, from the viewpoint of suppressing a decrease in the liquidus temperature and improving weather resistance, the total content of Mg ions, Ca ions, Sr ions and Ba ions is preferably 3.0% or more, more preferably 4.0% or more, even more preferably 4.5% or more, even more preferably 5.0% or more, even more preferably 5.5% or more, even more preferably 6.0% or more, even more preferably 6.5% or more, even more preferably 7.0% or more, even more preferably 7.5% or more, and even more preferably in the order of 8.0% or more, 8.5% or more and 9.0% or more.

[0036] In the above glass, from the viewpoint of suppressing the decrease in viscosity at the liquidus temperature, improving mechanical strength and / or suppressing the decrease in glass transition temperature, the cation ratio ((Mg ion + Ca ion + Sr ion + Ba ion) / (Li ion + Na ion + K ion)) of the total content of Mg ion, Ca ion, Sr ion and Ba ion to the total content of Li ion, Na ion and K ion is 0.100 or more, preferably 0.105 or more, more preferably 0.110 or more, even more preferably 0.115 or more, even more preferably 0.120 or more, even more preferably 0.125 or more, even more preferably 0.130 or more, and even more preferably 0.160 or more, 0.180 or more, 0.200 or more, 0.220 or more in this order. Suppressing the decrease in viscosity at the liquidus temperature is preferable from the viewpoint of improving the moldability of the glass. Furthermore, from the viewpoint of further improving the meltability and / or visible light transmittance, the cation ratio ((Mg ion+Ca ion+Sr ion+Ba ion) / (Li ion+Na ion+K ion)) is preferably 0.650 or less, more preferably 0.620 or less, even more preferably 0.590 or less, even more preferably 0.560 or less, even more preferably 0.530 or less, even more preferably 0.500 or less, even more preferably 0.460 or less, even more preferably 0.430 or less, even more preferably 0.400 or less, even more even more preferably 0.370 or less, and even more preferably 0.350 or less, 0.320 or less, 0.310 or less, 0.300 or less, 0.295 or less, 0.290 or less, 0.287 or less, and 0.285 or less, in this order. Furthermore, since an increase in the melting temperature of the glass makes it easier for Cu+ to be produced, resulting in a decrease in the visible light transmittance, it is preferable that the cation ratio is within the above range.

[0037] The Al ion content of the above glass can be 0%, 0% or more, or more than 0%. From the viewpoints of suppressing a decrease in Tg and improving mechanical strength and weather resistance, the Al ion content is preferably 1.0% or more, more preferably 1.3% or more, even more preferably 1.5% or more, even more preferably 1.7% or more, even more preferably 1.9% or more, even more preferably 2.1% or more, even more preferably 2.3% or more, and even more preferably 2.5% or more. In addition, in order to further increase the meltability of the raw material, Cu + From the viewpoint of further suppressing the generation of, the Al ion content is preferably 8.0% or less, more preferably 7.0% or less, more preferably 6.5% or less, even more preferably 6.0% or less, even more preferably 5.5% or less, even more preferably 5.3% or less, even more preferably 5.0% or less, even more preferably 4.7% or less, even more preferably 4.5% or less, even more preferably 4.0% or less, 2.5% or less, and 2.0% or less are preferable. The formal valence of the Al ion is +3. From the viewpoint of lowering the average valence and increasing the visible light transmittance, it is preferable that the Al ion content is low.

[0038] From the viewpoint of enhancing the thermal stability and mechanical strength of the glass, the total content of Al ions and P ions (Al ions + P ions) in the above glass is preferably 40.0% or more, more preferably 41.0% or more, even more preferably 42.0% or more, even more preferably 42.5% or more, even more preferably 43.0% or more, even more preferably 44.0% or more, even more preferably 44.5% or more, and even more preferably 45.0% or more. In addition, in order to further increase the meltability of the raw material and to increase the amount of Cu +From the viewpoint of further suppressing the generation of, the above total content (Al ions + P ions) is preferably 55.0% or less, more preferably 54.0% or less, even more preferably 53.0% or less, even more preferably 52.0% or less, even more preferably 51.0% or less, even more preferably 50.0% or less, even more preferably 49.5% or less, even more preferably 49.0% or less, even more preferably 48.5% or less, even more preferably 48.0% or less, even more preferably 47.0% or less, 46.5% or less, 46.2% or less, or even more preferably 46.0% or less.

[0039] The Zn ion content of the glass can be 0%, 0% or more, or more than 0%. From the viewpoint of lowering the Tg of the glass, the Zn ion content can be introduced in place of the Mg and / or Ca and / or Sr and / or Ba as long as it does not significantly affect the actions of the various components. However, from the viewpoint of improving weather resistance, the Zn ion content is preferably 8.7% or less, more preferably 8.5% or less, even more preferably 8.3% or less, even more preferably 8.0% or less, even more preferably 7.7% or less, even more preferably 7.5% or less, even more preferably 7.3% or less, even more preferably 7.1% or less, even more preferably 6.5% or less, even more preferably 6.0% or less, and even more preferably in the following order: 5.5% or less, 5.0% or less, 4.0% or less, 3.0% or less, 2.0% or less, and 1.0% or less. The formal valence of the Zn ion is +2.

[0040] From the viewpoint of improving weather resistance, the above-mentioned glass has a cation ratio of Zn ions to the total content of Mg ions, Ca ions, Sr ions, Ba ions, and Zn ions (Zn ions / (Mg ions+Ca ions+Sr ions+Ba ions+Zn ions)) of 0.600 or less, more preferably 0.580 or less, even more preferably 0.570 or less, still more preferably 0.560 or less, and further more preferably 0.550 or less, 0.540 or less, 0.530 or less, 0.520 or less, 0.510 or less, 0.505 or less, 0.500 or less, 0.498 or less, 0.496 or less, 0.400 or less, 0.300 or less, 0.200 or less, 0.100 or less, 0.080 or less, 0.060 or less, 0.040 or less, and 0.020 or less in this order. Furthermore, the cation ratio (Zn ions / (Mg ions+Ca ions+Sr ions+Ba ions+Zn ions)) may be 0 or 0.000.

[0041] The above glass is made by increasing the melting property of the raw material and adding Cu. + From the viewpoint of suppressing the generation of, the cation ratio of the total content of Al ions and P ions to the total content of Mg ions, Ca ions, Sr ions, Ba ions, Zn ions, and Cu ions ((Al ions + P ions) / (Mg ions + Ca ions + Sr ions + Ba ions + Zn ions + Cu ions)) is 5.3 or less, preferably 5.1 or less, more preferably 4.9 or less, even more preferably 4.7 or less, still more preferably 4.5 or less, and further more preferably in the order of 4.3 or less, 4.1 or less, 3.9 or less, 3.7 or less, 3.5 or less, 3.3 or less, and 3.1 or less. Furthermore, from the viewpoint of improving the thermal stability and mechanical strength of the glass, the above cation ratio ((Al ion+P ion) / (Mg ion+Ca ion+Sr ion+Ba ion+Zn ion+Cu ion)) is preferably 1.6 or more, more preferably 1.63 or more, even more preferably 1.65 or more, and further more preferably 1.68 or more, 1.7 or more, 1.75 or more, 1.8 or more, 1.85 or more, 2.00 or more, 2.20 or more, 2.40 or more, 2.60 or more, and 2.80 or more in this order.

[0042] The above glass may further contain, as cations, one or more of the following cations:

[0043] The introduction of a small amount of rare earth ions such as Y ions, La ions, Gd ions, and Yb ions into glass can contribute to further improving weather resistance, improving chemical resistance, suppressing the decrease in glass transition temperature, and / or suppressing the decrease in viscosity at the liquidus temperature. The content of these rare earth ions can be 0%, 0% or more, or more than 0%, and can be 3.0% or less, 2.0% or less, 1.0% or less, or 0.5% or less. The formal valence of Y ions, La ions, Gd ions, and Yb ions is +3.

[0044] The addition of small amounts of Ti, Zr, Nb, W and Bi is a component that contributes to improving the weather resistance and chemical resistance of the glass, as well as suppressing a decrease in Tg and a decrease in the liquidus viscosity. The Ti ion content can be 0%, 0% or more, or more than 0%, and is preferably 3.0% or less, more preferably 2.0% or less, even more preferably 1.0% or less, and even more preferably 0.5% or less. The formal valence of the Ti ion is +4. The Zr ion content may be 0%, 0% or more, or more than 0%, and is preferably 3.0% or less, more preferably 2.0% or less, even more preferably 1.0% or less, and even more preferably 0.5% or less. The formal valence of the Zr ion is +4. The Nb ion content can be 0%, 0% or more, or more than 0%, and is preferably 3.0% or less, more preferably 2.0% or less, even more preferably 1.0% or less, and even more preferably 0.5% or less. The formal valence of Nb ions is +5. The W ion content may be 0%, 0% or more, or more than 0%, and is preferably 3.0% or less, more preferably 2.0% or less, even more preferably 1.0% or less, and even more preferably 0.5% or less. The formal valence of the W ion is +6. The Bi ion content may be 0%, 0% or more, or more than 0%, and is preferably 3.0% or less, more preferably 2.0% or less, even more preferably 1.0% or less, and even more preferably 0.5% or less. The formal valence of the Bi ion is +3.

[0045] From the viewpoint of improving visible light transmittance, the above-mentioned glass has an average valence of cations excluding Cu ions and P ions that is less than 1.500, and is preferably 1.490 or less, more preferably 1.480 or less, even more preferably 1.470 or less, still more preferably 1.460 or less, still more preferably 1.450 or less, even more preferably 1.440 or less, still more preferably 1.430 or less, and even more preferably in the order of 1.420 or less, 1.410 or less, 1.400 or less, 1.390 or less, 1.380 or less, 1.370 or less, 1.360 or less, and 1.350 or less. From the viewpoint of suppressing a decrease in viscosity at the liquidus temperature, the average valence of cations other than Cu ions and P ions is preferably 1.100 or more, more preferably 1.1500 or more, more preferably 1.200 or more, even more preferably 1.250 or more, even more preferably 1.270 or more, even more preferably 1.280 or more, even more preferably 1.290 or more, and even more preferably 1.300 or more. For example, when changing the Cu concentration to adjust the glass thickness or the wavelength at which the transmittance is 50%, the composition can be readjusted by referring to the average valence.

[0046] The above average valence is calculated for cations other than Cu and P ions by dividing the sum of "the content in cation % of each cation x the formal valence of that cation" by the total content in cation % of cations other than Cu and P. For example, for a glass containing, in addition to Cu and P ions, A cation (formal valence a, content in cation % A%), B cation (formal valence b, content in cation % B%), and C cation (formal valence c, total content in cation % C%), the above average valence can be calculated as "(A×a+B×b+C×c) / (A+B+C)".

[0047] When changing the Cu concentration to adjust the glass thickness or the wavelength at which the transmittance is 50%, the average valence including Cu ions can also be referred to. From the viewpoint of further improving the visible light transmittance, the average valence of cations other than only P ions (hence including Cu ions) calculated in the same manner as above is preferably 1.550 or less, more preferably 1.540 or less, even more preferably 1.530 or less, even more preferably 1.520 or less, even more preferably 1.510 or less, even more preferably 1.500 or less, and even more preferably in the order of 1.490 or less, 1.480 or less, 1.470 or less, 1.460 or less, 1.450 or less, 1.440 or less, 1.430 or less, 1.420 or less, 1.410 or less, and 1.400 or less. Furthermore, from the viewpoint of suppressing a decrease in viscosity at the liquidus temperature, the average valence of cations excluding only P ions is preferably 1.300 or more, more preferably 1.310 or more, even more preferably 1.320 or more, still more preferably 1.330 or more, even more preferably 1.340 or more, even more preferably 1.350 or more, and even more preferably 1.360 or more.

[0048] (anions) The above glass contains O ions as a constituent ion. From the viewpoint of facilitating homogenization during glass melting and increasing productivity, the O ion content is 85.0% or more, preferably 90.0% or more, more preferably 95.0% or more, even more preferably 98.0% or more, and even more preferably 99.0% or more. In particular, from the viewpoint of suppressing volatilization during glass melting, increasing productivity, and suppressing the generation of harmful gases during production, the O ion content is preferably 100%. The formal valence of the O ion is -2.

[0049] In one embodiment, the glass may contain only O ions as anions, and in another embodiment, may contain O ions and one or more other anions. Examples of the other anions include F ions, Cl ions, Br ions, and I ions. The formal valence of F ions, Cl ions, Br ions, and I ions is -1.

[0050] From the viewpoints of improving the homogeneity and strength of the glass, the content of F ions is preferably 15.0% or less, more preferably 10.0% or less, even more preferably 5.0% or less, even more preferably 2.0% or less, and even more preferably 1.0% or less. In particular, from the viewpoints of suppressing volatilization during glass melting, increasing productivity, and suppressing the generation of harmful gases during production, F ions may be absent.

[0051] From the viewpoint of improving weather resistance, the above-mentioned glass has a ratio of the O ion content to the P ion content (O ion / P ion) of 3.300 or more, preferably 3.310 or more, more preferably 3.320 or more, even more preferably 3.330 or more, and further more preferably 3.340 or more, 3.350 or more, 3.360 or more, 3.370 or more, 3.380 or more, 3.390 or more, 3.400 or more, 3.410 or more, 3.420 or more, 3.430 or more, 3.440 or more, 3.450 or more, and 3.460 or more in this order. Furthermore, from the viewpoint of further improving the devitrification resistance and near-infrared light blocking ability during melting and forming of the glass, the above ratio (O ion / P ion) is preferably not more than 3.580, more preferably not more than 3.570, even more preferably not more than 3.560, still more preferably not more than 3.550, even more preferably not more than 3.540, even more preferably not more than 3.530, and furthermore, even more preferably not more than 3.520, 3.510 or less, 3.500 or less, and 3.490 or less, in that order.

[0052] The glass is preferably composed essentially of the above components, but may contain other components as long as the effects of the above components are not hindered. In addition, the glass may contain unavoidable impurities.

[0053] Pb, As, Cd, Tl, Be, and Se are all toxic, and therefore it is preferable that the above glass does not contain these as glass components.

[0054] U, Th, and Ra are all radioactive elements, and therefore it is preferable that the above glass does not contain these elements as glass components.

[0055] V, Cr, Mn, Fe, Co, Ni, Pr, Nd, Pm, Sm, Eu, Tb, Dy, Ho, Er, Tm, and Ce can increase the coloring of the glass and become a source of fluorescence. Therefore, in the above glass, the total content of these elements in terms of oxides based on the oxide glass is preferably 10 mass ppm or less, and it is more preferable that these elements are not contained as glass components.

[0056] Ge, Ta, and Gd are expensive raw materials, and therefore the above glass preferably does not contain these as glass components.

[0057] Sb (Sb2O3), Sn (SnO2), Ce (CeO2), and SO3 are optional elements that function as fining agents. Among these, Sb (Sb2O3) is a fining agent with a large fining effect. Sn (SnO2) and Ce (CeO2) have a smaller fining effect than Sb (Sb2O3). Adding a large amount of these fining agents tends to intensify the coloring of the glass. Therefore, when adding a fining agent, it is preferable to add Sb (Sb2O3) while taking into consideration the effect of coloring due to the addition.

[0058] The contents of the components capable of functioning as fining agents described below are expressed as values ​​calculated as oxides.

[0059] The content of Sb2O3 is expressed as an exclusive percentage. That is, when the total content of all glass components other than Sb2O3, SnO2, CeO2, and SO3 as oxides is taken as 100.0 mass%, the content of Sb2O3 in one embodiment can be less than 1.0 mass%, less than 0.5 mass%, 0.3 mass% or less, 0.2 mass% or less, 0.15 mass% or less, 0.1 mass% or less, or less than 0.1 mass%. In one embodiment, the content of Sb2O3 can be 0 mass%. In another embodiment, the content of Sb2O3 can be more than 0 mass%. During melting, Cu 2+From the viewpoint of suppressing coloration due to reduction and thereby increasing the visible light transmittance, the Sb2O3 content is preferably more than 0 mass%, and more preferably 0.01 mass% or more, 0.03 mass% or more, 0.05 mass% or more, 0.08 mass% or more, and 0.10 mass% or more, in that order.

[0060] The content of SnO2 is also expressed as an external percentage. That is, when the total content of all glass components other than SnO2, Sb2O3, CeO2 and SO3 as oxides is 100.0 mass%, the content of SnO2 is preferably less than 2.0 mass%, more preferably less than 1.0 mass%, even more preferably less than 0.5 mass%, and even more preferably less than 0.1 mass%. The content of SnO2 may be 0 mass%. By setting the content of SnO2 in the above range, the clarity of the glass can be improved.

[0061] The content of CeO2 is also expressed as an external percentage. That is, when the total content of all glass components other than CeO2, Sb2O3, SnO2 and SO3 as oxides is 100.0 mass%, the content of CeO2 is preferably less than 2.0 mass%, more preferably less than 1.0 mass%, further preferably less than 0.5 mass%, and even more preferably less than 0.1 mass%. The content of CeO2 may be 0 mass%. By setting the content of CeO2 in the above range, the clarity of the glass can be improved.

[0062] The SO3 content is also expressed as a percentage. 3、 When the total content of all glass components other than Sb2O3, SnO2, and CeO2 as oxides is taken as 100.0 mass%, the content of SO3 is preferably less than 2.0 mass%, more preferably less than 1.0 mass%, even more preferably less than 0.5 mass%, and even more preferably less than 0.1 mass%. The content of SO3 may be 0 mass%. By setting the content of SO3 in the above range, the clarity of the glass can be improved.

[0063] <Glass properties> (Transmittance characteristics) The above glass is suitable as a glass for a near-infrared cut filter. The near-infrared cut ability can be measured using the half-value, which is the wavelength at which the spectral transmittance becomes 50% at wavelengths of 600 nm or more, or the transmittance T1200 at a wavelength of 1200 nm can also be used as an index. The above glass can also exhibit high visible light transmittance, which can be measured using the transmittance T400 at a wavelength of 400 nm as an index. As will be described in detail later, in one embodiment, the above glass can be used as a glass for a near-infrared cut filter having a thickness of 0.25 mm or less. For glass (glass I) suitable for a near-infrared cut filter having a relatively thin thickness within the above thickness range, the half-value transmittance characteristics converted into a thickness of 0.11 mm is preferably 650 nm or less, and more preferably 647 nm or less, 645 nm or less, 643 nm or less, 641 nm or less, 640 nm or less, 639 nm or less, and 638 nm or less, in that order. For Glass I, the half-value transmittance characteristics converted into a thickness of 0.11 mm are preferably 600 nm or more, and more preferably 610 nm or more, 613 nm or more, 615 nm or more, 617 nm or more, 620 nm or more, 623 nm or more, 625 nm or more, and 628 nm or more in that order. With regard to Glass I, as the transmittance characteristics converted into a thickness of 0.11 mm, the transmittance T1200 at a wavelength of 1200 nm is preferably 42.0% or less, and more preferably, in this order, 41.0% or less, 40.0% or less, 39.0% or less, 38.5% or less, 38.0% or less, 37.5% or less, 37.0% or less, 36.5% or less, 36.0% or less, 35.5% or less, and 35.0% or less. For Glass I, the transmittance characteristics converted into a thickness of 0.11 mm are transmittance T1200 at a wavelength of 1200 nm, which can be, for example, 10.0% or more, 12.0% or more, or 14.0% or more. However, a lower such transmittance can be said to mean better near-infrared blocking ability, so it is also preferable that the transmittance be less than the above-exemplified values. Furthermore, for Glass I, in terms of transmittance characteristics converted into a thickness of 0.11 mm, the transmittance T400 at a wavelength of 400 nm is preferably 68.0% or more, more preferably 70.0% or more, and further more preferably in the order of 71.0% or more, 72.0% or more, 73.0% or more, 74.0% or more, 75.0% or more, 76.0% or more, 77.0% or more, 78.0% or more, 79.0% or more, and 80.0% or more. For Glass I, as the transmittance characteristics converted into a thickness of 0.11 mm, the transmittance T400 at a wavelength of 400 nm can be, for example, 98.0% or less, 97.0% or less, or 96.0% or less. A higher transmittance can be said to mean better visible light transmittance, so it is also preferable for the transmittance to exceed the above-mentioned values. Furthermore, for glass (glass II) suitable for a near-infrared cut filter having a relatively large thickness within the above thickness range, the half-value transmittance characteristics converted into a thickness of 0.21 mm is preferably 650 nm or less, and more preferably 647 nm or less, 645 nm or less, 643 nm or less, 641 nm or less, 640 nm or less, 639 nm or less, and 638 nm or less, in that order. For glass II, thickness 0. 2 As the transmittance characteristics converted into 1 mm, the half value is preferably 600 nm or more, and more preferably 610 nm or more, 613 nm or more, 615 nm or more, 617 nm or more, 620 nm or more, 623 nm or more, 625 nm or more, and 628 nm or more in that order. With regard to Glass II, as the transmittance characteristics converted into a thickness of 0.21 mm, the transmittance T1200 at a wavelength of 1200 nm is preferably 42.0% or less, and more preferably, in this order, 41.0% or less, 40.0% or less, 39.0% or less, 38.5% or less, 38.0% or less, 37.5% or less, 37.0% or less, 36.5% or less, 36.0% or less, 35.5% or less, and 35.0% or less. For Glass II, the transmittance characteristics converted into a thickness of 0.21 mm are transmittance T1200 at a wavelength of 1200 nm, which can be, for example, 10.0% or more, 12.0% or more, or 14.0% or more. However, a lower such transmittance can be said to mean better near-infrared blocking ability, and therefore it is also preferable for the transmittance to be below the above-exemplified values. Furthermore, for Glass II, in terms of transmittance characteristics converted into a thickness of 0.21 mm, the transmittance T400 at a wavelength of 400 nm is preferably 68.0% or more, more preferably 70.0% or more, and further more preferably in the order of 71.0% or more, 72.0% or more, 73.0% or more, 74.0% or more, 75.0% or more, 76.0% or more, 77.0% or more, 78.0% or more, 79.0% or more, and 80.0% or more. For Glass II, as the transmittance characteristics converted into a thickness of 0.21 mm, the transmittance T400 at a wavelength of 400 nm can be, for example, 98.0% or less, 97.0% or less, or 96.0% or less. Since a higher transmittance can be said to mean better visible light transmittance, it is also preferable that the transmittance exceed the above-mentioned values.

[0064] The transmittance characteristics are values ​​determined by the following method. The glass sample is processed to have parallel and optically polished flat surfaces, and the external transmittance at wavelengths of 200 to 1200 nm is measured. The external transmittance includes the reflection loss of light rays on the sample surface. The intensity of the light beam perpendicularly incident on one of the optically polished flat surfaces is defined as intensity A, and the intensity of the light beam emerging from the other flat surface is defined as intensity B, and the spectral transmittance B / A is calculated. The wavelength at which the spectral transmittance is 50% at wavelengths of 600 nm or more is defined as the half-value λ. T 50. The spectral transmittance at a wavelength of 400 nm is T400, and the spectral transmittance at a wavelength of 1200 nm is T1200. If the glass to be measured is not glass with a thickness that can be converted, the thickness of the glass is taken as d, and the transmittance at each wavelength λ is converted by the following formula. From the transmittance characteristics obtained by conversion, the half-value λ TConversion values ​​for T50, T400 and T1200 can be calculated.

[0065] T(λ)=(1-R(λ)) 2 ×exp(log e ((T0(λ) / 100) / (1-R(λ)) 2 )×d / d0)×100

[0066] In the formula, T(λ): converted transmittance (%) at wavelength λ, T0(λ): measured transmittance (%) at wavelength λ, d: Converted Thickness (mm), d0: Glass Thickness (mm), R(λ)=((n(λ)-1) / (n(λ)+1)) 2 where n(λ) is the reflectance at wavelength λ, and n(λ) is the refractive index at wavelength λ. Here, calculations are performed assuming constants of n(λ) = 1.51680 and R(λ) = 0.042165.

[0067] (weather resistance) The glass has the composition described above and thus exhibits excellent weather resistance. The weather resistance can be evaluated, for example, by the method described in the Examples below, and the evaluation result is preferably ⊚ or ◯, and more preferably ⊚.

[0068] (Solubility) The glass can also exhibit excellent meltability by having the composition described above. The meltability can be measured, for example, by the evaluation result of the meltability evaluated by the method described in the Examples below, and it is preferable that the evaluation result is ◯.

[0069] (Glass transition temperature Tg, temperature at which endothermic reaction converges Tm) The glass transition temperature of the above glass is not particularly limited. From the viewpoint of processability and / or imparting heat resistance in a subsequent step, the Tg is preferably 300° C. or higher, and more preferably 310° C. or higher, 320° C. or higher, 330° C. or higher, 340° C. or higher, and 350° C. or higher in that order. On the other hand, from the viewpoint of reducing the burden on the annealing furnace and the molding apparatus, the Tg is preferably 500°C or less, and more preferably 490°C or less, 480°C or less, 470°C or less, 460°C or less, 450°C or less, 440°C or less, 430°C or less, 420°C or less, 410°C or less, 400°C or less, and 390°C or less, in that order. The temperature Tm at which the endothermic reaction of the glass converges is not particularly limited, but the lower the Tm, the better the melting property tends to be. Also, the better the melting property, the higher the visible light transmittance of the glass tends to be. From these viewpoints, Tm is preferably 870°C or less, and more preferably 860°C or less, 850°C or less, 840°C or less, 830°C or less, 820°C or less, 810°C or less, 800°C or less, 790°C or less, 780°C or less, 770°C or less, 760°C or less, and 750°C or less in this order.

[0070] (specific gravity) A lightweight near-infrared cut filter is preferable because it leads to a reduction in the weight of an element or device that the filter is built in. From this point of view, the specific gravity of the glass is preferably 3.50 or less, and more preferably 3.45 or less, 3.40 or less, 3.35 or less, 3.30 or less, 3.25 or less, 3.20 or less, 3.15 or less, 3.10 or less, and 3.05 or less, in that order. The specific gravity can be, for example, 2.5 or more, or 2.6 or more, but from the above viewpoint, a low specific gravity is preferable, and therefore it is also preferable for the specific gravity to be lower than the values ​​exemplified here.

[0071] <Glass manufacturing method> The above glass can be obtained by mixing, melting, and molding various glass raw materials. For the production method, the description below can also be referred to.

[0072] The near-infrared absorbing glass is suitable as a glass for a near-infrared cut filter. The near-infrared absorbing glass can also be applied to optical elements (lenses, etc.) other than near-infrared cut filters, and can also be applied to various other glass products, and various modifications are possible.

[0073] [Near infrared cut filter] One aspect of the present invention relates to a near-infrared cut filter (hereinafter also simply referred to as "filter") made of the near-infrared absorbing glass described above.

[0074] The glass constituting the above filter is as described above.

[0075] A specific example of a method for manufacturing the above filter will be described below, however, the following manufacturing method is merely an example and does not limit the present invention.

[0076] The glass melt is prepared by weighing and mixing glass raw materials such as phosphates, oxides, carbonates, nitrates, sulfates, and fluorides to obtain a desired composition, and then melting the raw materials in a melting vessel such as a platinum crucible at, for example, 800°C to 1000°C. At this time, a lid such as platinum can be used to suppress the volatilization of volatile components. The melting can be carried out in the air, and in order to suppress the change in the valence of Cu, an oxygen atmosphere can be used or oxygen can be bubbled into the glass melt. The glass in the molten state becomes a homogenized glass melt with reduced bubbles (preferably no bubbles) due to stirring and fining.

[0077] The molten glass is stirred and clarified, and then poured out and formed into a desired shape. When pouring out the glass, it is preferable to lower the temperature to near the liquidus temperature to increase the viscosity of the glass, since this makes it difficult for convection to occur in the poured glass and makes it difficult for striae to form.

[0078] The glass can be formed by any known method such as casting, pipe pouring, rolling, pressing, etc. The formed glass is transferred to an annealing furnace preheated to near the glass transition point, and slowly cooled to room temperature. In this manner, a near-infrared cut filter can be produced.

[0079] An example of the molding method will be described below. A mold is prepared that is composed of a flat and horizontal bottom surface, a pair of side walls that face each other in parallel across the bottom surface, and a dam plate that blocks one of the openings located between the pair of side walls. Homogenized molten glass is poured into the mold from a platinum alloy pipe at a constant flow rate. The poured molten glass spreads in the mold and is formed into a glass plate restricted to a constant width by the pair of side walls. The formed glass plate is continuously drawn out from the opening of the mold. By appropriately setting the molding conditions such as the shape and dimensions of the mold and the flow rate of the molten glass, a large and thick glass block can be formed. The molded glass molded body is transferred to an annealing furnace that has been heated to near the glass transition temperature in advance, and is slowly cooled to room temperature. The glass molded body that has been slowly cooled to remove distortion is subjected to mechanical processing such as slicing, grinding, and polishing. In this way, a near-infrared cut filter having a shape according to the application, such as a plate shape or a lens shape, can be obtained. Alternatively, a method can be used in which a preform made of the above glass is molded, and the preform is heated, softened, and press molded (particularly a precision press molding method in which the final product is press molded without performing mechanical processing such as grinding and polishing on the optically functional surface). An optical multilayer film can be formed on the surface of the filter as necessary.

[0080] The near-infrared cut filter has both excellent near-infrared cut ability and high visible light transmittance, and is capable of satisfactorily correcting the color sensitivity of a semiconductor imaging device.

[0081] Moreover, the near-infrared cut filter can be applied to an imaging device by combining it with a semiconductor image sensor. The semiconductor image sensor is a package in which a semiconductor imaging element such as a CCD or a CMOS is mounted, and the light receiving section is covered with a light-transmitting member. The light-transmitting member can also be the near-infrared cut filter, or the light-transmitting member can be separate from the near-infrared cut filter.

[0082] The imaging device may also include an optical element such as a lens or a prism for forming an image of a subject on the light receiving surface of the semiconductor image sensor.

[0083] Furthermore, the near-infrared cut filter provides good color sensitivity correction, making it possible to provide an imaging device capable of obtaining images of excellent quality.

[0084] In one embodiment, the near-infrared cut filter can be a near-infrared cut filter having a thickness of 0.25 mm or less. In recent years, with the advent of smartphones, there has been a noticeable trend toward a reduction in the thickness of cameras of image pickup devices, and accordingly, it is desired that near-infrared cut filters also exhibit performance at thinner thicknesses. The near-infrared cut filter is also suitable as such a near-infrared cut filter. The thickness of the near-infrared cut filter can be 0.24 mm or less, 0.23 mm or less, 0.22 mm or less, 0.21 mm or less, 0.20 mm or less, 0.19 mm or less, 0.18 mm or less, 0.17 mm or less, 0.16 mm or less, 0.15 mm or less, 0.14 mm or less, 0.13 mm or less, or 0.12 mm or less. The thickness of the near-infrared cut filter can be, for example, 0.21 mm or 0.11 mm. The thickness of the near-infrared cut filter can be, for example, 0.50 mm or less. mm or more, but is not limited thereto. In the present invention and this specification, the "thickness" refers to the thickness of the sample in the region where the transmittance is measured, and can be measured by a thickness gauge, a micrometer, or the like. For example, the thickness may be measured at approximately the center of the position where the transmitted light passes, or the thickness may be measured at multiple points within the spot of the transmitted light and the average value may be calculated.

[0085] With respect to the near-infrared cut ability of the near-infrared cut filter, from the viewpoint of obtaining a near-infrared cut filter exhibiting even more excellent near-infrared cut ability, the value calculated as "thickness x Cu concentration" is preferably 0.2000 mol / m 2 More preferably, it is 0.2100 mol / m or more. 2 More than 0.2200mol / m2 More than 0.2300mol / m 2 More than 0.2400mol / m 2 More than 0.2500mol / m 2 More than 0.2600mol / m 2 More than 0.2700mol / m 2 More than 0.2800mol / m 2 More than 0.2900mol / m 2 More than 0.3000mol / m 2 More than 0.3100mol / m 2 More than 0.3150mol / m 2 More than 0.3200mol / m 2 More than 0.3250mol / m 2 The above order is more preferable. From the viewpoint of obtaining a near-infrared cut filter with a higher visible light transmittance, the value calculated as "thickness x Cu concentration" is set to 1.000 mol / m 2 It is preferable that the molecular weight is 0.9800 mol / m or less, and more preferably 0.9800 mol / m 2 Below, 0.9600mol / m 2 Below, 0.9400mol / m 2 Below, 0.9200mol / m 2 Below, 0.9000mol / m 2 Below, 0.8800mol / m 2 Below, 0.8600mol / m 2 Below, 0.8400mol / m 2 Below, 0.8200mol / m 2 Below, 0.8000mol / m 2 Below, 0.7800mol / m 2 Below, 0.7600mol / m 2 Below, 0.7400mol / m 2 Below, 0.7200mol / m 2 Below, 0.7000mol / m 2 Below, 0.6800mol / m 2 Below, 0.6600mol / m 2 Below, 0.6400mol / m 2 Below, 0.6200mol / m 2 Below, 0.6000mol / m 2Below, 0.5800mol / m 2 Below, 0.5600mol / m 2 Below, 0.5400mol / m 2 Below, 0.5200mol / m 2 Below, 0.5000mol / m 2 Below, 0.4800mol / m 2 Below, 0.4600mol / m 2 Below, 0.4800mol / m 2 Below, 0.4200mol / m 2 Below, 0.4100mol / m 2 Below, 0.4000mol / m 2 Below, 0.3900mol / m 2 Below, 0.3800mol / m 2 Below, 0.3700mol / m 2 Below, 0.3600mol / m 2 Below, 0.3500mol / m 2 The following order is more preferable:

[0086] The calculation method of the above "thickness x Cu concentration" will be explained. "Thickness x Cu concentration" = (specific gravity of the composition) / (molecular weight of the composition) x (cation % of Cu ions / 100) ×d / 10×10 4 The unit is mol / m 2 and d is the thickness (mm).

[0087] The calculation method for the molecular weight of the composition in the above formula will be explained below. (The molecular weight of the composition) is, for all components constituting the composition, (Molecular weight of each component based on cation) x (cation % of each component / 100) The unit is g / mol. Furthermore, the calculation method for the above (molecular weight of each component based on a cation) will be explained. (Molecular weight of each component based on a cation)= (Atomic weight of the element that makes up the cation) + (Atomic weight of oxygen x coefficient according to valence)

[0088] The coefficients according to the valence are as follows: If the formal valence is +1, the coefficient is 0.5 If the formal valence is +2, the coefficient is 1.0 If the formal valence is +3, the coefficient is 1.5 If the formal valence is +4, the coefficient is 2.0 If the formal valence is +5, the coefficient is 2.5 If the formal valence is +6, the coefficient is 3.0

[0089] The transmittance characteristics of the near-infrared cut filter can be referred to in the above descriptions of Glass I and Glass II. Also, the physical properties of the near-infrared cut filter can be referred to in the above descriptions of the near-infrared absorbing glass. EXAMPLES

[0090] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the embodiments.

[0091] [Examples 1 to 81 and Comparative Examples A to F] As glass raw materials, phosphates, fluorides, carbonates, nitrates, oxides, etc. were weighed and mixed so that 150g to 300g of glass having the composition shown in Table 1 was obtained, and the mixture was placed in a platinum crucible or a quartz crucible, melted at 800°C to 1000°C for 60 to 180 minutes, stirred to degas and homogenize, and then poured into a preheated mold and molded into a predetermined shape. The obtained glass molded body was transferred to an annealing furnace heated to the vicinity of the glass transition temperature and slowly cooled to room temperature. Test pieces were cut out from the obtained glass, and both sides were mirror-polished to a thickness of about 0.2 mm, and various evaluations were performed by the following methods.

[0092] [Evaluation method] <Transmittance characteristics> The transmittance of each test piece at wavelengths of 200 to 1200 nm was measured using a spectrophotometer. From the measurement results, the half-value (unit: nm), the transmittance at a wavelength of 1200 nm T1200 (unit: %), and the transmittance at a wavelength of 400 nm T400 (unit: %) were calculated as values ​​converted into thicknesses of 0.11 mm or 0.21 mm.

[0093] <Glass transition temperature Tg, temperature at which endothermic reaction converges Tm> Using a differential scanning calorimeter (DSC8270) manufactured by Rigaku, the glass transition temperature Tg and the temperature Tm at which the endothermic reaction due to melting converged were measured at a heating rate of 10° C. / min.

[0094] <Specific gravity> Specific gravity was measured by Archimedes' method.

[0095] <Weather resistance> Each test piece was kept in a thermohygrostat at a temperature of 85° C. and a relative humidity of 85% for 168 hours. After that, each test piece was visually evaluated for appearance under a fluorescent lamp. From the evaluation results, the weather resistance was evaluated according to the following criteria. ◎: No change in the surface is observed. ○: Clouding was observed on the surface, but no deliquescence was observed. ×: Deliquesced.

[0096] <meltability> The raw materials (mixture) were weighed and mixed in such a way that 200 g of glass was obtained after melting, using the same recipe as the glass raw materials used to prepare the test pieces, and then placed in a platinum crucible or a silica glass crucible and melted for 60 minutes at 1000° C. Visual observation showed that the melt was evaluated as “good” when no residual melt was obtained, and “bad” when residual melt was observed.

[0097] The above results are shown in Table 1 (Table 1-1 to Table 1-6), Table 2 (Table 2-1 to Table 2-6), and Table 3 (Table 3-1 to Table 3-6). In the tables, the unit of the (total) content of cations is cation %, and the unit of the (total) content of anions is anion %.

[0098]

Table 1-1

[0099]

Table 1-2

[0100]

Table 1-3

[0101]

Table 1-4

[0102]

Table 1-5

[0103]

Table 1-6

[0104]

Table 2-1

[0105]

Table 2-2

[0106]

Table 2-3

[0107]

Table 2-4

[0108]

Table 2-5

[0109]

Table 2-6

[0110]

Table 3-1

[0111]

Table 3-2

[0112]

Table 3-3

[0113]

Table 3-4

[0114]

Table 3-5

[0115]

Table 3-6

[0116] As glass raw materials, phosphates, fluorides, carbonates, nitrates, oxides, etc. were weighed and mixed so that 150g to 300g of glass having a composition containing 0.080 mass% Sb2O3 in the composition of Example 64 in Table 1 was obtained, and the glass was put into a platinum crucible or a quartz crucible, melted under the same melting conditions as in Example 64, stirred to degas and homogenize, and then poured into a preheated mold and molded into a predetermined shape. The obtained glass molded body was transferred to an annealing furnace heated to the vicinity of the glass transition temperature and slowly cooled to room temperature. A test piece was cut out from the obtained glass, and both sides were mirror-polished to a thickness of about 0.2 mm, and the transmittance characteristics were evaluated by the above method. The evaluation results were that the transmittance T1200 at a wavelength of 1200 nm was 27.9%, and the transmittance T400 at a wavelength of 400 nm was 87.4%, as values ​​at a thickness of 0.11 mm (converted). Comparing the above evaluation results with those of Example 64, it can be confirmed that the addition of Sb2O3 can suppress coloring and increase the visible light transmittance.

[0117] Finally, the above-mentioned aspects will be summarized.

[0118] According to one embodiment, the glass contains, as constituent ions, at least one ion selected from the group consisting of P ions, Cu ions, O ions, Li ions, Na ions, and K ions, and one or more ions selected from the group consisting of Mg ions, Ca ions, Sr ions, and Ba ions, and in a glass composition expressed in cation %, the content of Cu ions is 15.0 cation % or less, the content of P ions is 55.0 cation % or less, and the cation ratio of the total content of Al ions and P ions to the total content of Mg ions, Ca ions, Sr ions, Ba ions, Zn ions, and Cu ions ((Al ions + P ions) / (Mg ions + Ca ions + Sr ions) The near infrared absorbing glass has a cation ratio ((Mg ions + Ca ions + Sr ions + Ba ions) / (Li ions + Na ions + K ions)) of the total content of Mg ions, Ca ions, Sr ions and Ba ions to the total content of Li ions, Na ions and K ions of 0.100 or more, an average valence of cations excluding Cu ions and P ions is less than 1.500, and in the glass composition expressed as anion %, the content of O ions is 85.0 anion % or more and the ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.300 or more.

[0119] The above glass can be a near-infrared absorbing glass that has excellent near-infrared blocking ability, high visible light transmittance, and excellent weather resistance and meltability.

[0120] In one embodiment, in the glass composition of the above glass expressed in cation %, the content of P ions can be 30.0 cation % or more and 50.0 cation % or less.

[0121] In one embodiment, in the glass composition of the above glass expressed in cation %, the content of Li ions can be 10.0 cation % or more.

[0122] In one embodiment, in the glass composition of the above glass expressed in cation %, the content of Cu ions can be 2.1 cation % or more and 15.0 cation % or less.

[0123] In one embodiment, the ratio (O ions / P ions) can be 3.400 or more.

[0124] In one embodiment, in the glass composition of the above glass expressed in cation %, the cation ratio of Zn ions to the total content of Mg ions, Ca ions, Sr ions, Ba ions, and Zn ions (Zn ions / (Mg ions+Ca ions+Sr ions+Ba ions+Zn ions)) can be 0.600 or less.

[0125] In one embodiment, in the glass composition of the above glass expressed in anion %, the content of O ions can be 90.0 anion % or less.

[0126] In one embodiment, the glass can have a transmittance T1200 of 42.0% or less at a wavelength of 1200 nm, as a transmittance characteristic converted into a thickness of 0.11 mm.

[0127] In one embodiment, the glass can have a transmittance T400 of 68.0% or more at a wavelength of 400 nm, as a transmittance characteristic converted into a thickness of 0.11 mm.

[0128] In one embodiment, the glass can have a transmittance T1200 of 42.0% or less at a wavelength of 1200 nm, as a transmittance characteristic converted into a thickness of 0.21 mm.

[0129] In one embodiment, the glass can have a transmittance T400 of 68.0% or more at a wavelength of 400 nm, as a transmittance characteristic converted into a thickness of 0.21 mm.

[0130] According to one embodiment, there is provided a near-infrared cut filter made of the near-infrared absorbing glass described above.

[0131] In one embodiment, the near-infrared cut filter can have a thickness of 0.25 mm or less.

[0132] In one embodiment, the near infrared cut filter may have transmittance characteristics converted into a thickness of 0.11 mm such that the transmittance is 50% at wavelengths of 600 nm or more in the range of 600 nm to 650 nm.

[0133] In one embodiment, the near-infrared cut filter can have a transmittance T1200 of 42.0% or less at a wavelength of 1200 nm, as a transmittance characteristic converted into a thickness of 0.11 mm.

[0134] In one embodiment, the near-infrared cut filter can have a transmittance T400 of 68.0% or more at a wavelength of 400 nm, as a transmittance characteristic converted into a thickness of 0.11 mm.

[0135] In one embodiment, the near infrared cut filter may have transmittance characteristics converted to a thickness of 0.21 mm such that the transmittance is 50% at wavelengths of 600 nm or more in the range of 600 nm to 650 nm.

[0136] In one embodiment, the near-infrared cut filter can have a transmittance T1200 of 42.0% or less at a wavelength of 1200 nm, as a transmittance characteristic converted into a thickness of 0.21 mm.

[0137] In one embodiment, the near-infrared cut filter can have a transmittance T400 of 68.0% or more at a wavelength of 400 nm, as a transmittance characteristic converted into a thickness of 0.21 mm.

[0138] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. For example, by adjusting the composition of the above-mentioned glass compositions as described in the specification, a near infrared absorbing glass according to one aspect of the present invention can be obtained. Furthermore, it is of course possible to arbitrarily combine two or more of the items described in the specification as examples or preferred ranges.

Claims

1. The constituent ions are: P ions, Cu ions, O ion, One or more ions selected from the group consisting of Li ions, Na ions, and K ions, and one or more ions selected from the group consisting of Mg ions, Ca ions, Sr ions, and Ba ions; At least In the glass composition expressed in cation percentage, The content of Cu ions is 5.1 cation% or more and 15.0 cation% or less, The content of P ions is 30.0 cation% or more and 55.0 cation% or less, The content of Na ions is 0 cation% or more and 1.0 cation% or less, a cation ratio ((Al ion + P ion) / (Mg ion + Ca ion + Sr ion + Ba ion + Zn ion + Cu ion)) of the total content of Al ion and P ion to the total content of Mg ion, Ca ion, Sr ion, Ba ion, Zn ion and Cu ion is 5.300 or less, a cation ratio ((Mg ions + Ca ions + Sr ions + Ba ions) / (Li ions + Na ions + K ions)) of the total content of Mg ions, Ca ions, Sr ions and Ba ions to the total content of Li ions, Na ions and K ions is 0.100 or more, the average valence of cations other than Cu ions and P ions is less than 1.500; In the glass composition expressed as anion percentage, The content of O ions is 85.0 anion% or more, and A near-infrared absorbing glass having a ratio of the O ion content to the P ion content (O ion / P ion) of 3.300 or more.

2. 2. The near infrared absorbing glass according to claim 1, wherein the content of P ions in the glass composition expressed in cation % is 30.0 cation % or more and 50.0 cation % or less.

3. 3. The near infrared absorbing glass according to claim 1, wherein the content of Li ions in the glass composition expressed in cation % is 10.0 cation % or more.

4. 4. The near infrared absorbing glass according to claim 1, wherein the ratio (O ions / P ions) is 3.400 or more.

5. 5. The near infrared absorbing glass according to claim 1, wherein, in a glass composition expressed in cation%, a cation ratio of Zn ions to a total content of Mg ions, Ca ions, Sr ions, Ba ions, and Zn ions (Zn ions / (Mg ions+Ca ions+Sr ions+Ba ions+Zn ions)) is 0.600 or less.

6. 6. The near infrared absorbing glass according to claim 1, wherein in a glass composition expressed in anion %, a content of F ions is 10.0 anion % or less.

7. 7. The near infrared absorbing glass according to claim 1, wherein, as transmittance characteristics converted into a thickness of 0.11 mm, a wavelength at which the transmittance becomes 50% at wavelengths of 600 nm or more is in a range of 600 nm to 650 nm, a transmittance T1200 at a wavelength of 1200 nm is 42.0% or less, and a transmittance T400 at a wavelength of 400 nm is 68.0% or more.

8. 7. The near infrared absorbing glass according to claim 1, wherein, as transmittance characteristics converted into a thickness of 0.21 mm, a wavelength at which the transmittance becomes 50% at wavelengths of 600 nm or more is in a range of 600 nm to 650 nm, a transmittance T1200 at a wavelength of 1200 nm is 42.0% or less, and a transmittance T400 at a wavelength of 400 nm is 68.0% or more.

9. A near infrared cut filter comprising the near infrared absorbing glass according to any one of claims 1 to 6.

10. 10. The near infrared cut filter according to claim 9, which has a thickness of 0.25 mm or less.

11. The near-infrared cut filter according to claim 9 or 10, wherein the transmittance characteristics converted into a thickness of 0.11 mm are such that the wavelength at which the transmittance becomes 50% after 600 nm is in the range of 600 nm to 650 nm, the transmittance T1200 at a wavelength of 1200 nm is 42.0% or less, and the transmittance T400 at a wavelength of 400 nm is 68.0% or more.

12. The near-infrared cut filter according to claim 9 or 10, wherein the transmittance characteristics converted into a thickness of 0.21 mm are such that the wavelength at which the transmittance becomes 50% after wavelength 600 nm is in the range of 600 nm to 650 nm, the transmittance T1200 at a wavelength of 1200 nm is 42.0% or less, and the transmittance T400 at a wavelength of 400 nm is 68.0% or more.

Citation Information

Patent Citations

  • Filter glass for absorbing near infrared ray

    JP1982149845A

  • Near-infrared light cutting filter glass

    JP2011168455A

  • Glass

    JP2014125395A

  • Near-infrared radiation absorption glass

    JP2019038719A

  • Near-infrared cut filter glass and process for manufacturing same

    WO2012018026A1